2017
DOI: 10.1007/s12371-017-0231-6
|View full text |Cite
|
Sign up to set email alerts
|

The Landscape Attractiveness of Abandoned Quarries

Abstract: This study is a trial for presenting high attractiveness of shape form in abandoned quarry areas, as well as for indicating social interest in the areas in terms of their attractiveness. For this reason, a procedure of evaluation of the landscape attractiveness of abandoned quarries is suggested, which was created by assigning additional partial criteria, and their comparison with the criteria of already existing methods. Methods used for the research are as follows: the semantic differential technique (also c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 7 publications
(7 reference statements)
0
41
0
Order By: Relevance
“…Margiotta and Sanso [27] confirmed that some abandoned quarries are part of the natural and cultural heritage as an important resource for geotourism development. Baczynska et al [28] also confirmed these landscape forms (quarries) as elements that enrich the value of particular areas in terms of tourism. Authors of the study [26,29] concluded that abandoned quarries could be of geoconservation significance and some of them were very important for geoscientific tourism.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Margiotta and Sanso [27] confirmed that some abandoned quarries are part of the natural and cultural heritage as an important resource for geotourism development. Baczynska et al [28] also confirmed these landscape forms (quarries) as elements that enrich the value of particular areas in terms of tourism. Authors of the study [26,29] concluded that abandoned quarries could be of geoconservation significance and some of them were very important for geoscientific tourism.…”
Section: Discussionmentioning
confidence: 89%
“…Specific anthropogenic processes result in anthropogenic landforms (e.g., quarries, pits, communication cuttings and underground landforms) that can be considered important from the 2 of 16 scientific, educational, cultural, historical, environmental and tourism point of view [13][14][15]. These landforms have multiple functions: -They can be seen as elements that increase the overall landscape diversity [16] and positively influence biodiversity [17,18], especially disused quarries and flooded pits); -They provide information about landscape changes and modifications made in the past, and these can be an important resource for understanding the cultural and technical level of a society [19,20]; -They support an ecosystem service provisioning [21]; -They allow us to trace the use of geodiversity in the past and interpret cultural heritage in relation to abiotic nature [22], including the involvement of local communities [23,24] based on applying of historical ecology [25]; -They possess the potential for developing sustainable forms of tourism (or geotourism), which can positively affect local economic development [26,27]-they can be visually attractive [28] or allow us to interpret the technical aspects of using geodiversity resources, e.g., mining and industrial tourism [29,30]; -They allow us to observe stratigraphical, tectonic, palaeopedological and other Earth science features that would normally remain hidden and unrecorded in the literature or on geological maps [31,32] and the information can be used in both formal and informal education, and it is important from the conservation point of view [33]; -Landforms can be considered as an important stepping stones for biological species sensitive to fragmentation of landscape [34,35]; -Specific anthropogenic landforms form an inseparable part of items of cultural heritage, e.g., earth fortifications and ramparts and irrigation channels [36,37]; -In urban areas, the anthropogenic landforms allow us to interpret urban development [38] and they are an inseparable component of urban landscapes [39].…”
Section: Introductionmentioning
confidence: 99%
“…The significant, positive effects of quarrying that have been appreciated over the last several decades concern the role of quarries as geological and geomorphological heritage (geoheritage) sites with the potential for geoscientific education (e.g., Petersen 2002) and geotourism (e.g., Newsome & Dowling 2006;Pralong 2005;López-García et al 2011;Baczyńska et al 2017;Stefano & Paolo 2017). Abandoned quarries perceived as geological and geomorphologic heritage sites enable a society to study old quarry sites and their technical infrastructure as historical objects to understand both the variability in approaches and techniques for quarrying over time and quarrying's specific impacts on the Earth's surface.…”
Section: Quarries As Objects For Geotourismmentioning
confidence: 99%
“…However, a newly created form may constitute a landscape diversion with a positive, intriguing or even inspiring impact on our senses (Baczyńska et al 2017). In this case, the above-mentioned negative associations cannot be applied.…”
Section: Introductionmentioning
confidence: 99%